The module of developing communicative competence of seventh and eighth-grade students in uzbekistan secondary schools - Tuychibayeva, Gulnoza; Kukiboyeva, Mahliyo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article focuses on developing communicative competence among seventh and eighth-grade students in Uzbekistan’s secondary schools, proposing a specialized module aimed at enhancing language skills. Given the rising demand for English skills globally, this study examines current teaching practices, identifies challenges, and proposes solutions to improve students’ communicative competence. Using a mixed-method approach, data was collected from 50 secondary schools in Uzbekistan through teacher surveys, language assessments, classroom observations, and interviews with administrators. Findings indicate that traditional grammar-based teaching methods are dominant, with limited use of communicative language teaching (CLT) approaches. Many students struggle with speaking and listening tasks, which are essential components of communicative competence. The proposed module includes task-based activities, interactive speaking exercises, and real-life communication scenarios aimed at addressing gaps in current methodologies. Teacher training programs are also recommended to ensure effective CLT implementation. The paper concludes that shifting to a communicative approach and enhancing resources and teacher preparation can significantly improve students’ language skills, better preparing them for academic and social challenges in a globalized society.